Influence of operating parameters on overall system efficiencies using solid oxide electrolysis technology. (15th June 2015) - Peters, Roland; Deja, Robert; Blum, Ludger; Nguyen, Van Nhu; Fang, Qingping; Stolten, Detlef
Abstract: In future, a high proportion of electrical energy will be generated from renewable sources. One option for using electricity generated from renewable sources, for example from wind power or photovoltaics, is to produce hydrogen by electrolysis. Different system configurations and operating conditions were investigated in order to study the efficiencies of producing hydrogen by solid oxide electrolysis. Important factors for system efficiencies are the voltage at which the stack is operated, the source of heat for the water evaporation, the pressure level of the hydrogen storage, and the system configuration. Based on these factors, four efficiencies were defined taking into account the different conditions and configurations. The calculated efficiencies vary from 104% in the best case down to 62% in the worst case, all based on the lower heating value of the hydrogen produced. Highlights: An SOEC system is modeled with a cathode recycling loop. Variants are examined with three different cell voltages and three recycling ratios. Efficiency is mainly influenced by the source of heat, the cell voltage, the storage pressure, and the recycling ratio. Efficiency varies from 104% down to 62% based on the lower heating value of the hydrogen produced.